Effects of hydrodynamic shear stress on sludge properties, N2O generation, and microbial community structure during activated sludge process. (15th November 2020) - Yan, Xu; Zheng, Shikan; Yang, Jie; Ma, Jiahui; Han, Yunping; Feng, Jinglan; Su, Xianfa; Sun, Jianhui
Abstract: Sludge properties are critical to the treatment performance and potentially correlate with nitrous oxide (N2 O) generation during activated sludge processes. The hydrodynamic shear stress induced by aeration has a significant influence on sludge properties and is inevitable for wastewater treatment plants (WWTPs). In this study, the effects of aerobic induced hydrodynamic shear stress on sludge properties, N2 O generation, and microbial community structure were investigated using three parallel sequencing batch reactors (SBRs) with identical dissolved oxygen (DO) concentrations. Results showed that with a shear stress increase from 1.5 × 10 −2  N/m 2 to 5.0 × 10 −2  N/m 2, the COD and NH4 + -N removal rates were enhanced from 89.4% to 94.0% and from 93.9% to 98.0%, respectively, while the TN removal rate decreased from 66.0% to 56.5%. Settleability of the activated sludge flocs (ASFs) also increased with the enhancement of shear stress, due to variation in sludge properties including particle size, regularity, compactibility, and EPS (extracellular polymeric substances) composition. The increase in shear stress promoted oxygen diffusion within the ASFs and mitigated NO2 − -N accumulation, leading to a decrease in the N2 O–N conversion rate from (4.8 ± 0.3)% to (2.2 ± 0.6)% (based on TN removal). Microbial analysis results showed that the functional bacteria involved in the biological nitrogen removal was closely related with shear stress. The increase in shear stress favored the enrichment of nitrite oxidizing bacteria (NOB) while suppressed the accumulation of ammonia-oxidizing bacteria (AOB) and denitrifying bacteria (DNB). Graphical abstract: Image 1 Highlights: The influence of shear stress on the properties of sludge flocs were investigated. Shear stress benefits COD and NH4 + -N removal but disadvantages denitrification. Nitrous oxide generation is mitigated by the increase in shear stress. The oxygen transfer resistance within ASFs was reduced by the enhanced shear stress. The contents of functional bacteria involved in N removal varied by the shear stress.